2015
DOI: 10.2136/sh15-02-0006
|View full text |Cite
|
Sign up to set email alerts
|

Use of Olive Mill Pomace Biochar as a Support for Soil Microbial Communities in an Italian Sandy Soil

Abstract: Soils with low organic matter and modest biological activity exhibit a reduced capacity to produce goods and services. The use of biochar as a soil amendment has been suggested as a way to increase soil productivity thanks to its physical and chemical characteristics. These properties lead to its possible use as a structural support and a habitat for microorganisms. This study investigated the role of biochar, produced from olive mill pomace at the Mediterranean Agronomic Institute of Bari by a slow pyrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that the biochar produced from OMSW is a promising sorbent/immobilizing agent for removing heavy metals from aqueous solutions or to remediate heavy metal contaminated soils [26, 29]. Additionally, the enhancing effects of OMSW biochar on soil microbial biomass C and N, and alteration of the structure of the bacterial community has been reported by other authors [30, 31]. However, to date, there is no available information on the effects of OMSW-derived biochar on nutrient availability in alkaline sandy soils.…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies have demonstrated that the biochar produced from OMSW is a promising sorbent/immobilizing agent for removing heavy metals from aqueous solutions or to remediate heavy metal contaminated soils [26, 29]. Additionally, the enhancing effects of OMSW biochar on soil microbial biomass C and N, and alteration of the structure of the bacterial community has been reported by other authors [30, 31]. However, to date, there is no available information on the effects of OMSW-derived biochar on nutrient availability in alkaline sandy soils.…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, converting OMSW into biochar could reduce surface pollution on one hand, and the produced biochar could serve as a soil conditioner for enhanced soil productivity on the other hand. Previous studies have demonstrated the enhancing effects of OMSW-derived biochar on soil microbial biomass C and N, and alteration of the structure of the bacterial community in soil [ 25 , 26 ]. However, to date, there is no available information on the effects of OMSW-derived biochar on nutrient availability in alkaline sandy soils.…”
Section: Introductionmentioning
confidence: 99%